Planetary healthy publics after COVID-19. Issue 4 (April 2021) - Hinchliffe, Stephen; Manderson, Lenore; Moore, Martin
Summary: COVID-19 is a sign of a global malaise. The pandemic is an outcome of what we term a planetary dysbiosis, for which underlining drivers include inequality and the exploitation and extraction of human and non-human labours. The implication is that the usual fixes to outbreaks of infectious diseases (ie, surveillance, pharmaceutical measures, and non-pharmaceutical measures) will be insufficient without a thorough reappraisal of and investment in planetary health. Given the heterogeneity and diversity of environments and populations, we envisage these actions as a matter for the generation of new kinds of public, requiring widespread and multiple forms of engagement to generate lasting solutions. We use and extend the concept of healthy publics to suggest a movement that can start to reclaim planetary health as a collective and ongoing issue.